Analisa Analitis Karateristik Arus Motor DC yang Disuplai Penyearah Dioda Satu Fasa - Vicky Salamena (ARIKA, 2011)
This study intends to look at the characteristics of current drawn by the dc motor when supplied by a single- phase diode rectifier. Characteristics of this current will depend on the output of a single-phase sinusoidal rectifier and electrical characteristics of dc motors. Assessments carried out by modeling a single-phase diode rectifier in order to obtain output voltage equation. Next modeled as a series dc motor electric ekiuvalen thus obtained mathematical model. By using Kirchoff Voltage Law is obtained first order differential equation is not homogeneous due to the excitation voltage ac source. This equation contains the parameters of the current as a function of time. Electric current equation is then simulated to obtain the dc motor input current curve as a function of time or current dc motor moment. The result is a instantanous current characteristic curve dc motor function of time, steady-state current at t = 0, and the average current which is a dc currents.